Physicochemical Characteristics and SPF Value of Kepok Banana Corm Extract Cream - Andini; Mega Rilen; Viona Masakana; Ellyvina Dini (Universitas Muhammadiyah Malang, 2024)
Banana Corm is banana plant waste that has not been utilized optimally and contains flavonoids which have the potential as natural UV repellents. This study aims to determined the physical-chemical characteristics and preferences of respondents as well as the SPF value of kepok banana corm extract creams. Three cream formulations were carried out using concentration variants of 10% (F1), 20% (F2) and 30% (F3) with physical property tests including organoleptic tests, cream type tests, homogeneity tests, spreadability tests, centrifugation tests and SPF value. The test results show that the three formulations have different colors and aromas and are o/w cream types and have a homogeneous texture. All formulas meet the skin's pH range. In the test results there was a significant difference (p<0.05) in the order of highest spreading power in diameter F3 (5.725 ± 0.01 cm) × F2 (5.24 ± 0.2 cm) × F1 (5.24 ± 0.092 cm ), whereas for the centrifugation test results there was no phase separation in the supply. The results of respondents' preferences for cream showed that the overall cream preparation formula is acceptable and liked by respondents. Based on the research results, it can be concluded that the banana bongol extract cream meets the physical quality requirements based on predetermined parameters and the banana bongol extract cream can be accepted by respondents. Cream with variations in banana weevil concentration of 10%, 20% and 30%, obtained an SPF value in the maximum protection category